Annual survey of industries 2021-2022 volume-1 - Govt. of India, Ministry of Statistical and Programme Implementation, National Statistical Office; National Statistical Office (Kolkata: Industrial Statistics Wing, 2024)
The ASI 2020-21 publications contain detailed results of factory scctor in two volumes. Volume I of the publication presents data relating to capital, employment, emoluments and several other economic parameters relevant to industrial sector such as (i) number of factories (ii) fixed/working capital (iii) total input (iv) total output (v) depreciation (vi) net value added etc. Volume l of the publication provides details on materials consumed and ex-factory value of products and by-products both at all India level as well as at the level of State/UTs. While Volume I is uploaded on the website of the Ministry (www.mospi.gov. in), Volume lI is a CD-ROM publication. In addition to Volume I& Volume , Summary Results of Factory Sector" is also brought out as a separate publication based on ASI2020-21 results for easy comprehension.
Preface -- Contents -- Section 1 : Introduction -- Section 2 :Highlights -- Table1: Estimate of selected characteristics of factory sector by 4-digit industry class (NIC- 2008) for all-India -- Table2: Estimate of selected characteristics of factory sector by 3-digit industry group (NIC-2008)for each state/UT -- Table2a: Estimate of selected characteristics of factory sector by 2-digit industry division (NIC-2008)for each state/UT -- Table2b: Estimate of selected characteristics of factory sector by 2-digit industry division (NIC-2008)for all-India -- Table3: Estimate of (i) employment, (ii) mandays employed and (iii) emoluments paid in the factory sector by their type for each 4-digit industry class(NIC-2008) for all-India -- Table4: Estimate of (i) employment, (ii) mandays employed and (iii) emoluments paid in the factory sector by their type for each 3-digit industry class(NIC-2008) for each state/UT -- Table4a: Estimate of (i) employment, (ii) mandays employed and (iii) emoluments paid in the factory sector by their type for each 2-digit industry class(NIC-2008) for each state/UT -- Table5: Fuels consumed in the factory sector by type of fuel for each 4-dugut industry class (NIC-2008) for all-India -- Table6: Fuels consumed in the factory sector by type of fuel for each 3-digut industry class (NIC-2008) for each state/UT -- Table6a: Fuels consumed in the factory sector by type of fuel for each 2-digut industry class (NIC-2008) for each state/UT -- Table7: Estimate of structural ratios and technical coefficients for factory sector during 2017-18 to 2021-22 -- Table8: Estimate of RSE for few basic parameters at 2-digit industry division (NIC-2008) for all-India
Keywords: Annual report; Industry